2020
DOI: 10.1038/s41586-020-03069-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of nucleosomal H3K36 methylation by NSD methyltransferases

Abstract: The NSD family histone methyltransferases, including NSD1, NSD2 and NSD3, play crucial roles in chromatin regulation and are implicated in oncogenesis 1 , 2 . NSD enzymes exhibit an auto-inhibitory state that is relieved by nucleosome engagement, allowing for H3K36 di-methylation catalysis 3 – 7 . However, the molecular basis underlying this mechanism is largely unknown. Here, we have solved the cryo-EM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
128
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(142 citation statements)
references
References 42 publications
8
128
0
Order By: Relevance
“…The NSD family exhibits higher enzymatic activity and H3K36 selectivity with nucleosome substrate compared with the histone substrates [ 79 , 91 , 92 ]. Consistent with these observations, NSD2 and NSD3 undergo conformational changes in the autoinhibitory loop region upon nucleosome binding [ 93 , 94 ]. In the absence of nucleosome binding, the autoinhibitory loop is stabilised in the active site of NSD2 or NSD3 through inhibitory interactions with the SET domain [ 93 , 94 ].…”
Section: The Auto-inhibitory State Of H3k36 Methyltransferases Is Relieved By Their Own Subunits and Possibly Chromatinmentioning
confidence: 61%
See 1 more Smart Citation
“…The NSD family exhibits higher enzymatic activity and H3K36 selectivity with nucleosome substrate compared with the histone substrates [ 79 , 91 , 92 ]. Consistent with these observations, NSD2 and NSD3 undergo conformational changes in the autoinhibitory loop region upon nucleosome binding [ 93 , 94 ]. In the absence of nucleosome binding, the autoinhibitory loop is stabilised in the active site of NSD2 or NSD3 through inhibitory interactions with the SET domain [ 93 , 94 ].…”
Section: The Auto-inhibitory State Of H3k36 Methyltransferases Is Relieved By Their Own Subunits and Possibly Chromatinmentioning
confidence: 61%
“…In the absence of nucleosome binding, the autoinhibitory loop is stabilised in the active site of NSD2 or NSD3 through inhibitory interactions with the SET domain [93,94]. Upon nucleosome binding, the SET domain interacts with the histones and the nucleosomal DNA to replace the interaction with the autoinhibitory loop [93,94]. Consequently, the autoinhibitory loop is pushed away from the active site, making the substrate-binding site accessible.…”
Section: Allosteric Regulation Of the H3k9 Methyltransferase Suv39h1 mentioning
confidence: 99%
“…One way in which genes are controlled is through the addition of various chemical marks to DNA and DNA-associated proteins. Writing in Nature, Yuan et al 1 and Li et al 2 show that one of the enzymes that deposit such marks, NSD3, is mutated and hyperactive in some human cancers -a finding that suggests new avenues for treating people with the diseases.…”
mentioning
confidence: 99%
“…Figure 1 | Deregulation of histone methylation in human cancer.The enzyme NSD3 is a histone methyltransferase -it dimethylates (adds two methyl groups to) histone H3 proteins, around which DNA is packaged. Yuan et al1 have found that NSD3 is dysregulated in human squamous cell lung carcinoma, and Li et al2 have unravelled the structural mechanism involved. a, In 'NSD3-addicted cancers', the enzymatic activity of NSD3 is increased through an increase in the number of copies of the NSD3 gene, or through mutations that cause hyperactive enzyme activity (not shown).…”
mentioning
confidence: 99%
“…However, extensive efforts to target the SET domains of NSD proteins with potent inhibitors have proven unsuccessful at the nano-molar scale. In this regard, a recent Cryo-EM study revealed that a series of residues within and flanking the SET domain are crucial for unwrapping the linker and nucleosomal DNA such that an autoinhibitory state inherent to NSD proteins is converted to an active conformation 35,36 . Understanding these unique features of NSDs could further facilitate the structurally-assisted design of new inhibitors.…”
mentioning
confidence: 99%